Abnormal Mechanisms of Plasticity and Metaplasticity in Autism Spectrum Disorders and Fragile X Syndrome - Oberman, Lindsay M. (J Child Adolesc Psychopharmacol, 2016)
Objectives: Multiple lines of evidence from genetic linkage studies to animal models implicate aberrant cortical plasticity and metaplasticity in the pathophysiology of autism spectrum disorder (ASD) and fragile X syndrome (FXS). However, direct experimental evidence of these alterations in humans with these disorders is scarce. Transcranial magnetic stimulation (TMS) is a noninvasive tool for probing mechanisms of plasticity and metaplasticity in vivo, in humans. The aim of the current study was to examine mechanisms of plasticity and metaplasticity in humans with ASD and FXS. We employed a repetitive TMS protocol developed specifically to probe cortical plasticity, namely continuous theta burst stimulation (cTBS). Methods: We applied a 40-second train of cTBS to primary motor cortex (M1) to healthy control participants and individuals with ASD or FXS, and we measured the cTBS-induced modulation in motor-evoked potentials (MEPs) in a contralateral intrinsic hand muscle. Each participant completed two sessions of the same protocol on two consecutive days. The degree of modulation in MEPs after cTBS on the first day was evaluated as a putative index of cortical plasticity. Examination of the changes in the effects of cTBS on the second day, as conditioned by the effects on the first day, provided an index of metaplasticity, or the propensity of a given cortical region to undergo plastic change based on its recent history. Results: After a 40-second cTBS train, individuals with ASD show a significantly longer duration of suppression in MEP amplitude as compared with healthy controls, whereas individuals with FXS show a significantly shorter duration. After a second train of cTBS, 24 hours later, the ASD group was indistinguishable from the control group, and while in the FXS group MEPs were paradoxically facilitated by cTBS. Conclusion: These findings offer insights into the pathophysiology of ASD and FXS, specifically providing direct experimental evidence that humans with these disorders show distinct alterations in plasticity and metaplasticity, consistent with the findings in animal models. If confirmed in larger test–retest studies, repeated TMS measures of plasticity and metaplasticity may provide a valuable physiologic phenotype for ASD and FXS.